An assessment of private General Practitioners contracting for public health services delivery in O.R. Tambo District, South Africa - Charles Hongoro; Itumeleng N. Funani; Wezile Chitha; Lizo Godlimpi (AOSIS, 2015)
Low- and middle-income countries are striving towards universal health coverage in a variety of ways. Achieving this goal requires the participation of both public and the private sector providers. The study sought to assess existing capacity for independent general practitioner contracting in primary care, the reasons for the low uptake of government national contract and the expectations of general practitioners of such contractual arrangements. This was a case study conducted in a rural district of South Africa. The study employed both quantitative and qualitative data collection methods. Data were collected using a general practitioner and practice profiling tool, and a structured questionnaire. A total of 42 general practitioners were interviewed and their practices profiled. Contrary to observed low uptake of the national general practitioner contract, 90% of private doctors who had not yet subscribed to it were actually interested in it. Substantial evidence indicated that private doctors had the capacity to deliver quality care to public patients. However, low uptake of national contarct related mostly to lack of effective communication and consultation between them and national government which created mistrust and apprehension amongst local private doctors. Paradoxically, these general practitioners expressed satisfaction with other existing state contracts. An analysis of the national contract showed that there were likely to benefit more from it given the relatively higher payment rates and the guaranteed nature of this income. Proposed key requisites to enhanced uptake of the national contract related to the type of the contract, payment arrangements and flexibility of the work regime, and prospects for continuous training and clinical improvements. Low uptake of the national General Practitioner contract was due to variety of factors related to lack of understanding of contract details. Such misunderstandings between potential contracting parties created mistrust and apprehension, which are fundamental antitheses of any effective contractual arrangement. The idea of a one-size-fits-all contract was probably inappropriate.